Combustion of Lean Flammable Mixtures in an Intense Radiation Field - MIZUTANI, Yukio; YOSHIDA, Tomoki; ADACHI, Kazumi (Nihon Kikai Gakkai rombunshuu. B hen, 1988)
A combustion process showing a slow temperature rise was realized in an intense radiation field by burning a lean combustible mixture in a cylindrical combustion chamber lined with a refractory in which a permeable plate was placed at the upstream and downstream ends, respectively. It was found by the measurement of the temperature and composition of gas along with the ion current and by high-speed schlieren photography, that a laminar flame was attached to the lower part of the red-hot refractory surface and that it spread towards the upper central portion, even if the mixture strength was below the lean flammable limit. The flame becomes convex toward the unburnt mixture due to some instability resulting in a kind of cellular structure. The flickering of the flame due to the wavy motion of the flame base and the cellular structure is the cause of the slow temperature rise.